Manajemen Sumber Daya Manusia Strategis dalam Peningkatan Kualitas Pendidikan Anak Usia Dini - Revita Yanuarsari; Dhini Sri Widia Mulyani; Intan Astria; Dimas Firdaus Kusuma W; Saktika Rohmah Fajarwati (Pusat Riset dan Inovasi Nasional, 2025)
Early Childhood Education (ECED) is an important foundation for the development of children during the golden period, so the success of its implementation is largely determined by the quality of human resources (HR) involved. Human Resource Management (HRM) plays a crucial role in ensuring the availability of educators and education personnel who are professional, competent, and able to provide meaningful services for child development.This study aims to analyze the concepts, challenges, and best practices of HRM in PAUD institutions. The method used is a literature study with a descriptive qualitative approach through reviewing journals, books, and scientific publications related to education and ECD management. The results of the study show that HRM practices in PAUD include the process of planning the needs of educators, selective recruitment, development through continuous training, competency-based performance appraisal, provision of appropriate compensation, and motivation and retention strategies. However, there are still significant challenges, including limited quality and quantity of educators, budget limitations, and barriers to the implementation of holistic-integrative ECD programs. Therefore, HR management in ECD needs to be done strategically, integrated, and collaboratively between government, educational institutions, and communities. In conclusion, effective HR management